A prototype AlInP electron spectrometer. (1st October 2021) - Whitaker, M.D.C.; Butera, S.; Lioliou, G.; Krysa, A.B.; Barnett, A.M.
Abstract: The development and characterization of a prototype temperature tolerant (capable of operation up to at least 100 ​°C) particle counting electron spectrometer with an AlInP detector is reported. This is the first time that the response of an AlInP detector to electrons (β − particles) has been reported. The detector was a custom made circular mesa (200 ​μm diameter) Al0.52 In0.48 P p + -i-n + (2 ​μm i layer) photodiode; this was coupled to a custom made low-noise charge-sensitive preamplifier and otherwise standard readout electronics. The detector was electrically characterized and the spectrometer was investigated for its response to illumination from a 63 Ni radioisotope β − particle source over the temperature range 100 ​°C–20 ​°C. The absorbed electron energy within the active region (i layer) of the AlInP detector and the expected to be detected spectra were calculated using Monte Carlo simulations. Comparisons between the simulated and measured spectra indicated that the response of the spectrometer was in agreement with the Monte Carlo model. Future generations of electron spectrometers of this type are expected to be useful for space science missions where the instrumentation would be subject to high temperatures and intense radiation (e.g. to study the radiolytic processes in comets close to perihelion). In order to inform development of future generations of AlInP electron detectors for such applications, the response of the prototype instrument to illumination with solar wind electrons was modelled within the experimentally verified energy range of the detector; avenues of future development to improve AlInP detector performance, identified from the presently reported results, was investigated and discussed. Highlights: An AlInP detector was demonstrated as capable of spectroscopic electron detection. The spectrometer operated at ≤ 100 ​°C, under illumination of β − particles ≤66 ​keV. Monte Carlo simulations informed β − particle spectra predicted to be detected. Experimentally measured and predicted spectra were in agreement. Avenues of future development to improve AlInP detector performance are discussed.